A VHF Radio for Software Defined Radio Applications. (2016) - Nambissan, T. Jishnu; Nikhil, T.V.; Vinodkumar, V.
Abstract: Modern communication circuits use a variety of modulation schemes. The technology is changing day by day and new technologies are emerging. The use of various modulation schemes makes compatibility a problem. Also the radio systems have to become intelligent to make them adapt to various channel characteristics and noise. To reduce these problems and to make the communication systems operate under various conditions, Software Defined Radios is a viable option. They are highly reconfigurable and their use of software to perform modulation and demodulation makes them suited to the communication demands of the modern world. Here we present a Software Defined Radio that operates in the VHF range. It is very compact and is capable of achieving good sideband rejection, frequency stability and medium bandwidth operations. It is suited to a wide range of modulation schemes and is very flexible.